Joint Modeling of Response Accuracy and Time in Between-Item Multidimensional Tests Based on Bi-Factor Model - Guo, Xiaojun; Huang, Zhengzheng; Liu, Tiechuan (Frontiers in Psychology, 2022)
With the popularity of computer-based testing, it is easier to collect item response times (RTs) in psychological and educational assessments. RTs can provide an important source of information for respondents and tests. To make full use of RTs, researchers have invested substantial effort in developing statistical models of RTs. Most of the proposed models posit a unidimensional latent speed to account for RTs in tests. In psychological and educational tests, many tests have been shown to be multidimensional, either deliberately or inadvertently. There may be general effects in between-item multidimensional tests. However, there currently exists no RT model that considers the general effects to analyze between-item multidimensional test RTs data. Simultaneous there is no joint hierarchical model that integrates RT and response accuracy (RA) for evaluating the general effects of between-item multidimensional tests. Therefore, a bi-factor joint hierarchical model using between-item multidimensional test is proposed in this study. Parameter recovery using simulation, indicating that the Hamiltonian Monte Carlo (HMC) algorithm works well. Meanwhile, the information criteria showed that the bi-factor hierarchical model (BFHM) is the best fit model. This means that it is necessary to take into consideration the general effects (general latent trait) and the multidimensionality of the response time in between-item multidimensional tests.